A Prefatory Sustainability Assessment of One-Part Geopolymers - Ooi Wan-En; Liew Yun-Ming; M.M. Al Bakri Abdullah; Ong Shee-Ween; Hang Yong-Jie; Tee Hoe-Woon; Lim Jia Ni (Archives of Metallurgy and Materials)
This study investigated the sustainability aspect of the fly ash (FA)-based one-part geopolymers (OPGs) with various combinations and amount of alkali activators (AA). The three groups of OPG were: the M-OPG activated with solely sodium metasilicate-anhydrous (Na2SiO3), the MH-OPG with Na2SiO3 and sodium hydroxide (NaOH), and the MC-OPG with Na2SiO3 and sodium carbonate (Na2CO3). The compressive strength, embodied carbon, embodied carbon index, embodied energy and embodied energy index were identified. Test result shows that the M-OPG and MC-OPG with the AA/FA ratio of 0.20 attained 83 MPa and 75 MPa of compressive strengths, respectively. The MH-OPG with AA/FA ratio of 0.15 attained 72 MPa of compressive strength. The embodied carbon and embodied energy of the OPGs were mainly contributed by the Na2SiO3-anhydrous. The values were lowered when the Na2SiO3-anhydrous were partially substituted with NaOH or Na2CO3. Increasing the AA content increased the embodied carbon and energy. The embodied carbon index (3.80 kg CO2/m3/MPa) and embodied energy index (14.72 MJ/m3/MPa) of the MC-OPG with AA/FA ratio of 0.20 were the lowest. The outcome of this study supports the utilisation of Na2CO3 to partially substitute Na2SiO3 for the development of OPGs.